Evaluation of antioxidant contents and proximate compositions of purslane (portulaca oleracea l.) at different growfh stages - Tay, Li Quan (2016)
Purslane (Portulaca oleracea L.) is an attractive candidate as a useful vegetable crop and as a cosmetic ingredient containing elevated quantity of nutrients, highly rich In antioxidant properties. Due to limited information to date on nutritional quality of purslane, experiment was conducted at the Faculty of Sustainable Agriculture, Universiti Malaysia Sabah to evaluate the antioxidant content and proximate composition of purslane (Portulaca oleracea L.) at different growth stages. The experiment was conducted in polybags filled with top soil in the rainshelter structure of Faculty of Sustainable Agriculture, UMS, campus Sandakan. The soil had electrical conductivity of 1.15 dS m-1 and pH of 5.23 and 22.02% of organic carbon. Plant samples were harvested at interval of 15 day for two months which were at day 15, 30, 45 and 60. The experimental design was conducted using Completely Randomized Design (CRD) with six replications. The treatment means were compared by Least Significance Differences (LSD) at 5 % significant level. Physical characteristic of P. oleracea at each stage of maturity showed significant differences (p<0.05) in plant height, leaf length, leaf width, stem diameter, shoot fresh and dry weight. Total phenolic content of purslane was found to be highest at 15 days with the value 4.54 mg GAE/g while 45 days purslane has the highest total flavonoid content which was 22.22 mg QE/g. Highest ash content was found at 15 day old purslane which was 20.50 % while highest crude protein and crude fat was found at 30 day purslane plant with the value 32.46 % and 7.67 % respectively. The level of ash, crude protein and crude fat was found to decrease (p<O.05) with advanced plant maturity. While crude fibre In P. oleracea Increased Significantly (p<O.05) with plant maturity.